Military Laser Technology and Systems. - Titterton, D. H. (Artech House, 2015)
This new resource provides an insight into the physical principles of the device technology that underpins many laser-based military systems in one form or another. From this knowledge a deeper understanding of the fundamental requirements and the potential performance, as well as limitations of such systems may be assessed, given the appropriate operational parameters.Engineers and students are provided with practical advice on how to evaluate laser devices and systems, operate them safely, and train with them.
Keywords: Weapons systems.; Lasers -- Military applications.; Laser weapons.; elektronické knihy; electronic books